2023
DOI: 10.1158/0008-5472.c.6511497.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from p38γ MAPK Is Essential for Aerobic Glycolysis and Pancreatic Tumorigenesis

Abstract: <div>Abstract<p>KRAS is mutated in most pancreatic ductal adenocarcinomas (PDAC) and yet remains undruggable. Here, we report that p38γ MAPK, which promotes PDAC tumorigenesis by linking KRAS signaling and aerobic glycolysis (also called the Warburg effect), is a novel therapeutic target. p38γ interacted with a glycolytic activator PFKFB3 that was dependent on mutated KRAS. KRAS transformation and overexpression of p38γ increased expression of PFKFB3 and glucose transporter GLUT2, conversely, silen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Among 4 isozymes (PFKFB1-4), PFKFB3 has the highest kinase:phosphatase activity ratio and is the most potent isozyme to enhance glycolysis, whose activity is regulated both at the transcriptional and post-transcriptional levels [36,37,38]. Interestingly, PFKFB3 is upregulated by mutant KRAS, which is well described to enhance glycolysis [39]. We found that PFKFB3 was activated through PKA-mediated phosphorylation, downstream of (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
“…Among 4 isozymes (PFKFB1-4), PFKFB3 has the highest kinase:phosphatase activity ratio and is the most potent isozyme to enhance glycolysis, whose activity is regulated both at the transcriptional and post-transcriptional levels [36,37,38]. Interestingly, PFKFB3 is upregulated by mutant KRAS, which is well described to enhance glycolysis [39]. We found that PFKFB3 was activated through PKA-mediated phosphorylation, downstream of (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%